THE EFFECTIVENESS OF YOGA RELAXATION TECHNIQUES TO REDUCE THE ANXIETY LEVEL OF PREGNANT MOTHERS PRIMIGRAVIDA TRIMESTER III - Marchatus Soleha; Indah Rahmadania (Universitas Negeri Gorontalo, 2022)
One of the psychological disorders that can occur in pregnant women is anxiety disorders, anxiety is a feeling of worry, nervousness, or anxiety about something with uncertain results and can accompany, influence, or cause depression. This study aims to determine the effectiveness of yoga relaxation techniques in overcoming anxiety in third-trimester primigravida pregnant women. Method This research is quantitative, using a quasi-experimental design with one group pretest-posttest. This research was conducted at BPM Fauziah Hatta in 2016. The population in this study were all third-trimester primigravida pregnant women who had an examination at BPM Fauziah Hatta Palembang. Samples were taken by purposive sampling of as many as 40 respondents with criteria for gestational age of 28-36 weeks. the questionnaire used is the standard HARS (Hamilton Anxiety Rating Scale) questionnaire. After the data was collected, the data were analyzed univariately and bivariate using the paired T-test statistic. Results: before being given treatment, respondents with severe anxiety levels were 23 people (57.5%) and very severe anxiety was 12 people (30%), moderate anxiety was 4 people (10%), and mild anxiety was only 1 person (2.5 %). After being given treatment, most of the respondents who did not have anxiety were 25 people (62.5%), respondents with mild anxiety were 12 people (30%) and severe anxiety was 1 person (2.55%). Conclusion: pregnant women with severe anxiety levels can reduce their anxiety to mild anxiety by doing yoga relaxation techniques, pregnant women's anxiety levels can decrease by 2.67 times by doing yoga relaxation techniques.